DETERMINANTS OF ISLAMIC FINANCIAL EXCLUSION IN INDONESIA - Ali, Mohammad Mahbubi; Devi, Abrista; Bustomi, Hamzah (Journal of Islamic Monetary Economics and Finance, 2020)
The study aims to uncover the determinants of Islamic financial exclusion in Indonesia by gathering the response from financially-excluded respondents. A total of 110 respondents were surveyed, representing five provinces, namely West Java, South Sulawesi, Aceh, East Kalimantan, and North Maluku. The criteria of financially-excluded respondents are those who do not have any Islamic financial products, neither saving, financing, nor capital market account. The study employs Confirmatory Factor Analysis (CFA) to identify indicators explaining Islamic financial exclusion determinants in Indonesia. The paper found that location is the key barrier to obtain financing from and participate in saving in Islamic banks/Islamic microfinance, while lack of financial knowledge is identified as the critical barrier to deal with Islamic capital market products. Overall, most of the respondents perceive human capital, as well as product and services as the two most significant determinant of Islamic financial exclusion in Indonesia, followed by infrastructure, policies and regulation, financial literacy, social influence, and religious commitment, respectively. The originality of the paper lies in detailed insight into the perception of financially-excluded on the factors leading to Islamic financial exclusion.